Systematic review of hepatitis C virus prevalence and incidence among HIV-positive men who have sex with men (MSM) in England - Sarah Savić-Kallesøe; David Palma Díaz; Andres Roman-Urrestarazu (Elsevier, 2021)
Background: Hepatitis C virus (HCV) infection is a leading cause of hepatitis C, liver cancer, and cirrhosis. It is treatable with directing acting antivrials (DAAs), yet still accounts for over 580,000 global deaths annually. Due to the nature of transmission and particular risk factors, men living with HIV who have sex with other men (HIV+ MSM) are disportionately burdened. Whilst HCV is a statutorily notifiable disaease in England and a virtually complete registry exists, data specific to MSM are not captured, leaving gaps in our knowledge of HCV trends among HIV+ MSM. Methods: This paper aims to investigate the HCV prevalence and incidence among HIV+ MSM in England through a systematic review of academic literature. Results: The systematic review resulted in six articles. Evidence suggests that incidence has generally risen between 2002-2015 and declined between 2015-2018, which may be attributed to the introduction of DAAs. The range of reported prevalences varied from 2.2%-9.9% , the most recent estimate being 4.24% in 2018. Conclusions: This review's deficiency is the non-existent record of behavioural risk factors across the studies. Most studies recruited HIV+ MSM from HIV clinics, an arguably robust sampling method considering that 90% of those living with HIV in England are engaged in care at an HIV clinic. The gaps in the academic literature and national surveillance for HCV among HIV+ MSM demonstrate this group to be disproportionately under-studied. National surveillance ought to record HCV cases and risk factors specific to HIV+ MSM to better inform interventions.